Rapid and cost effective development of SSR markers using next generation sequencing in Indian major carp, Labeo rohita (Hamilton, 1822) - Sahu, B P; Patel, A; Sahoo, L; Das, Paramananda; Meher, P; Jayasankar, P (Indian Journal of Fisheries, 2012)
Development of species specific microsatellite markers using conventional approaches such as partial and enriched genomic library screening are costly and time consuming. Next generation sequencing is a promising methodology for acquisition of abundant microsatellites from the genome. In an effort to enrich the present microsatellite database for marker map generation in Labeo rohita, Roche-454 GS-FLX sequencing platform was used and results were compared with the enriched library screening. A library enriched for 'GT' repeat was prepared and screened using Sanger sequencing. Screening of enriched library produced 1840 clones resulting in only 238 sequences having enough flanking region for primer designing. Roche- 454 sequencing of 10 MB of rohu genome generated 387 sequences containing microsatellite repeat with enough flanking region. Enriched library preparation, screening and Sanger sequencing took nearly one and half year, whereas data generation by next generation sequencing took just two months. Moreover equally good number of markers could be generated by high throughput sequencing platform which worked out to be one third cheaper.